The composition of mixed surfactants and cationic polymer/surfactant mixtures adsorbed at the air-water interface - Penfold, J; Staples, E; Tucker, I; Creeth, A; Hines, J; Thompson, L; Cummins, P; Thomas, R; Warren, N (Elsevier, 1997)
The use of specular neutron reflection and small-angle neutron scattering (SANS) to determine the composition of mixed surfactants and polymer/surfactant mixtures, absorbed at the air-water interface, in micelles and polymer or micellar complexes, is described. For the characterisation of adsorption at the air-water interface by neutron reflectivity, the emphasis is predominantly on the concentration regime where the surface is in equilibrium with a bulk aggregated phase; that is, for concentrations greater than the cmc of the mixture. This is a regime that is difficult to access by standard experimental techniques. The SANS measurements of micelle composition are an important complement to the reflectivity measurements in the understanding of mixed surfactant adsorption. Recent results on the anionic/non-ionic surfactant mixture of sodium dodecyl sulphate (SDS) and hexaethylene monododecyl ether (C 12E 6) in the absence and presence of the cationic polymer and on the non-ionic mixture of monododecyl/triethylene glycol (C 12E 3)/monododecyl octaethylene glycol (C 12E 8) illustrate the power and advantages of neutron scattering techniques.